The Role of E-Filing Policies, Tax Sanctions, and Taxpayer Awareness in Enhancing Individual Taxpayer Compliance - Pratiwi, Esti Utami; Arisa, Lisa; Ainasya, Aprilia Risma; Fazri, Edward (Jurnal Riset Akuntansi Terpadu, 2025)
This study examines the impact of e-filing policies, tax sanctions, and taxpayer awareness on individual taxpayer compliance at the East Serang Pratama Tax Service Office. Using a quantitative approach and multiple regression analysis, the research explores relationships among these factors based on primary data obtained from questionnaire surveys distributed to 60 registered individual taxpayers actively using electronic filing (e-filing). Empirical findings indicate that e-filing policies positively influence taxpayer compliance, primarily by enhancing convenience, efficiency, and transparency in tax reporting processes. The imposition of tax sanctions also demonstrates a significant positive relationship, underscoring their effectiveness as enforcement tools to ensure taxpayers adhere to regulatory standards. Furthermore, increased taxpayer awareness strongly correlates with improved compliance, reflecting the crucial role of knowledge and understanding in fostering voluntary compliance behavior. The study provides empirical evidence contributing to the existing literature on taxation compliance determinants within the Indonesian tax administration context. It highlights the importance of enhancing taxpayer education programs and continuously promoting electronic filing systems to optimize compliance. Tax authorities should further develop targeted strategies to raise taxpayer awareness, consistently apply sanctions, and simplify e-filing mechanisms, ultimately supporting higher compliance levels and achieving national revenue targets.